PENGARUH MEREK, HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN DI PT. JAYA TIMUR - Santo Santo; Syaifullah Syaifullah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine whether the brand, price and product quality affect customer loyalty PT. East Jaya. The number of respondents in this study were 147 customers who were taken as research samples. The data collection technique used is a questionnaire then the data taken is analyzed using the SPSS version 25 application. Based on the results of the analysis, it can be concluded that there is a brand influence on customer loyalty at PT. Jaya Timur positively or significantly with a t value of -4.066 > t table -1.97646 and the significance value of the brand variable is 0.000 < 0.05, the effect of price on customer loyalty PT. Jaya Timur positively or significantly with a t-count value of 3.101 > t-table 1.97646 and the significance value of the price variable is 0.002 <0.05, the influence of product quality on customer loyalty PT. Jaya Timur positively or significantly with a t-count value of 22.911 > t-table 1.97646 and the significance value of the product quality variable is 0.000 <0.05, and finally there is a simultaneous influence between brand, price and product quality on customer loyalty PT. Jaya Timur positively or significantly with a calculated f value of 230.233 > f table 3.06